2016
DOI: 10.3390/molecules21070921
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Provides Quality Characterization of Commercial Gochujang (Fermented Pepper Paste)

Abstract: To identify the major factors contributing to the quality of commercial gochujang (fermented red pepper paste), metabolites were profiled by mass spectrometry. In principal component analysis, cereal type (wheat, brown rice, and white rice) and species of hot pepper (Capsicum annuum, C. annuum cv. Chung-yang, and C. frutescens) affected clustering patterns. Relative amino acid and citric acid levels were significantly higher in wheat gochujang than in rice gochujang. Sucrose, linoleic acid, oleic acid, and lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Importantly, SPME has the ability to extract VOCs from fermented foods, including soy sauce, soy paste, and related beverages [5,7,10,11]. Metabolomics has also been used to evaluate the nutritional quality of foods, plants, or fermentation products [12][13][14]. Recently, we have reported the time-correlated dynamic metabolomes and VOC profiles for the acetous fermentative production stages of vinegar employing the GC-TOF-MS and HS-SPME-GC-MS analyses [15].…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, SPME has the ability to extract VOCs from fermented foods, including soy sauce, soy paste, and related beverages [5,7,10,11]. Metabolomics has also been used to evaluate the nutritional quality of foods, plants, or fermentation products [12][13][14]. Recently, we have reported the time-correlated dynamic metabolomes and VOC profiles for the acetous fermentative production stages of vinegar employing the GC-TOF-MS and HS-SPME-GC-MS analyses [15].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have also examined the metabolites and functionality of gochujang Values are mean ± SE (n = 10). produced using different koji types Lee, Suh, et al, 2016). Gochujang product prepared using wheat koji has high contents of amino acids and sugar, whereas gochujang product prepared using rice koji has high contents of flavonoids, LysoPCs, and GABA .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have also found that bioactive compounds showed different patterns and bioactive properties depending on cereal types (Lee, Lee, et al, ; Lee, Shin, et al, ; Lee, Suh, Jung, & Lee, ; Shin et al, ). They used giant embryonic rice (GE rice), a mutant rice, YR233517Acp79, with an enlarged embryo and contains higher γ‐oryzanol, tocopherol, GABA, protein vitamins, essential amino acids, and minerals compared with normal embryonic rice (NE rice) (Chung, Lee, & Kang, ; Chung, Lo, Nam, Jin, & Kang, ; Seo et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolomic studies coupled with chemometric methods including PCA and PLS regression analysis have been used to explore the relationships between the metabolome of diverse plant species and their genotypes, origins, vintages, qualities, and other specific attributes [ 94 , 95 , 96 , 97 , 98 , 99 ]. MP techniques are often used to evaluate the nutraceutical (nutritional or physiological) value of a single plant cultivar for quality control and breeding.…”
Section: Evaluation Of Green Tea Functionality Based On Its Composmentioning
confidence: 99%